Bumblefest - "Cowley, Joy" (Hawthorn; Mimosa/McGraw-Hill, 2007)
Sir Brian Flockart is a gentle knight who would rather be a peasant and grow cabbages and potatoes. He hates dangerous activities like swinging a battleaxe, horseriding and using sharp implements. So he has a problem when he's challenged by Sir Roger Duckbury, Bumblefest's jousting champion. How will Meg, the dairymaid, and Grund, the friendly dragon, help Sir Brian stay out of trouble?
Donated by "Book Planet", Dated 18-4-2025.
Keywords: knighthood Juvenile fiction